Outcomes of infants with congenital diaphragmatic hernia by side of defect in the FETO era - Ali, Kamal; Dassios, Theodore; Syed Abd Hamid, Syed Abdul Khaliq; Williams, Emma E.; Tamura, Kentaro; Davenport, Mark; Greenough, Anne (Springer Verlag, 2019)
Purpose To compare the outcomes of infants with a right (RCDH) versus a left-sided (LCDH) congenital diaphragmatic hernia (CDH) and whether these differed according to whether the infants had undergone fetoscopic tracheal occlusion (FETO). Methods Demographics, the type of surgical repair, preoperative and postoperative courses and respiratory, gastrointestinal, surgical and skeletal morbidities at follow-up were compared between infants with a RCDH or LCDH. A sub-analysis was undertaken in those who had undergone FETO. Results During the study period, there were 167 infants with a LCDH and 24 with a RCDH; 106 underwent FETO (15 RCDH). Overall, the need for inhaled nitric oxide (p = 0.036) was higher in the RCDH group and, at follow-up, infants with RCDH were more likely to have a hernia recurrence (p = 0.043), pectus deformity (p = 0.019), scoliosis (p = 0.029) and suffer chronic respiratory morbidity (p = 0.001). There were, however, no significant differences in short term or long term outcomes (hernia recurrence (p = 0.237), pectus deformity (p = 0.322), scoliosis (p = 0.0174) or chronic respiratory morbidity (p = 0.326)) between infants with a right or left sided CDH who had undergone FETO. Conclusion Overall, infants with a RCDH compared to those with a LCDH had greater long-term morbidity, but not if they had undergone FETO.